Digital technologies in Distance Education: phases, models, platforms and tools (Research, Society and Development, 2020)
Distance Education goes back a long time, although in its beginnings, the main form of interconnection between the agent who teaches and the one who learns was effected by correspondence via mail, unlike today, where connections are made through the internet. In this work we aim, through a bibliographic review, to trace a history of these new technologies, their models, types and virtual learning environments currently used in Distance Education. We approach Distance Education in a descriptive and analytical way, especially in Brazil, where even though these courses have existed since the beginning of the last century, it was only in 1996 that the Secretariat for Distance Education (SEED/MEC) was created, aiming at democratization of Brazilian education. We discussed the evolutionary phases of Distance Education, identified as to their means of integration between the parties, starting with correspondence, going through radio, television, synchronous communications, audio, video and computer teleconferences and, finally, for the use of the internet (fifth generation). As for distance learning models, there are numerous variations and adaptations of virtual learning environments (VLE), subsidized by new digital technologies, represented by numerous software and applications that facilitate interactivity and leverage online teaching-learning relationships. However, it is necessary to note that the utilization and evolution of distance education requires special attention in the process of implementing and managing the courses. This requires a careful preparation of interdisciplinary teams, since it permeates among these digital technologies the apprentice, who must represent the focal point in any teaching-learning process.